IMPLEMENTATION OF PHARMACY STANDARD SERVICE AND RELATED FACTORS IN BENGKULU CITY - Laksono, Heru; Susilo, Avrilya Iqoranny; Muslim, Zamharira; Ningsih, Lisma; Febriyanto, Tedy (Avicenna: Jurnal Ilmiah, 2023)
Introduction: The current development of pharmaceutical science has caused a shift in the orientation of pharmaceutical services from managing drugs as commodities to comprehensive services (pharmaceutical care). Pharmacists are not only drug managers but in a broader sense, include the implementation of rational drug use in the context of patient safety. Method: This research is an analytical observational study with a cross sectional design. The research population in this study were pharmacies operating in Bengkulu City, with samples taken using a purposive sampling technique taking into account the activeness of pharmacies in sending reports. Data collection was carried out by interviewing research respondents using a questionnaire. The Pharmaceutical Service Standard variable uses pharmaceutical standard indicators by referring to Minister of Health Regulation Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies. Results and Discussion: Overall research results show that pharmaceutical service standards in Bengkulu City pharmacies have not been implemented properly. The results obtained were that there were still 54% of pharmacies that had not implemented service standards for providing information to support the correct and rational use of medicines, monitoring the use of medicines to find out the final destination, as well as the possibility of medication errors. Conclusion: The existence of pharmaceutical service standards in pharmacies aims to improve the quality of pharmaceutical services; guarantee legal certainty for pharmaceutical personnel; and properly protect patients and the pharmaceutical community. The factor that hinders the implementation of pharmaceutical service standards in Bengkulu City pharmacies is the number of prescriptions that must be served every day (p value = 0.039, OR= 2.131). Keyword : Pharmacy ; Pharmaceutical Care; Standard of Service